Fe(OTf)3-catalyzed tandem Meyer-Schuster rearrangement/intermolecular hydroamination of 3-aryl propargyl alcohols for the synthesis of acyclic β-Aminoketones. Issue 13 (30th March 2017) - Tao, Ruiheng; Yin, Yan; Duan, Yongbin; Sun, Yuxing; Sun, Yue; Cheng, Fengkai; Pan, Jinpeng; Lu, Cheng; Wang, Yuan
Abstract: Fe(OTf)3 -catalyzed synthesis of acyclic β-aminoketones from 3-aryl propargyl alcohols and nitrogen nucleophiles were investigated. Results showed that propargyl alcohols without bulky groups α to the hydroxyl group underwent the transformation smoothly. Sulphonamides exhibited the higher reactivity than amides as the nitrogen nucleophiles and the transformation of acyclic β-aminoketones were finished in shorter reaction time and higher yields. Finally, racemic fluoxetine was efficiently accessed with the present reaction as the first step. This novel synthesis of acyclic β-aminoketones probable proceeded a Fe(OTf)3 -catalyzed Meyer-Schuster rearrangement of 3-aryl propargyl alcohols, followed by a intermolecular hydroamination between nitrogen nucleophiles and α, β-unsaturated ketones. Graphical abstract: